A place to call home: perspectives on offender community reintegration. Issue 4 (14th November 2016) - Tarpey, Emma; Friend, Hannah
Abstract : Purpose: The purpose of this paper is to explore offenders' experiences of community reintegration facilitated by a supported housing scheme. Design/methodology/approach: Data were derived from five semi-structured interviews with prolific offenders who were participating in a UK "north west housing association" scheme; a community reintegration programme for offenders released from prison. Findings: Thematic analysis demonstrated four predominant themes, these were: "the decision to change", "self-fulfilment", "a place to call home" and "a suitable support system". The themes are discussed in relation to the Good Lives Model. Practical implications: Participation in the housing scheme was a key component of the reintegration process, which positively facilitated lifestyle change. Originality/value: This research considers the often "unheard" perspectives of prolific offenders and highlights the significant role of community housing schemes in supporting successful community reintegration.